Latent HIV-1 is activated by exosomes from cells infected with either replication-competent or defective HIV-1. Issue 1 (December 2015) - Arenaccio, Claudia; Anticoli, Simona; Manfredi, Francesco; Chiozzini, Chiara; Olivetta, Eleonora; Federico, Maurizio
Abstract Background Completion of HIV life cycle in CD4+ T lymphocytes needs cell activation. We recently reported that treatment of resting CD4+ T lymphocytes with exosomes produced by HIV-1 infected cells induces cell activation and susceptibility to HIV replication. Here, we present data regarding the effects of these exosomes on cells latently infected with HIV-1. Results HIV-1 latently infecting U937-derived U1 cells was activated upon challenge with exosomes purified from the supernatant of U937 cells chronically infected with HIV-1. This effect was no more detectable when exosomes from cells infected with HIV-1 strains eithernef -deleted or expressing a functionally defective Nef were used, indicating that Nef is the viral determinant of exosome-induced HIV-1 activation. Treatment with either TAPI-2, i.e., a specific inhibitor of the pro-TNFα-processing ADAM17 enzyme, or anti-TNFα Abs abolished HIV-1 activation. Hence, similar to what previously demonstrated for the exosome-mediated activation of uninfected CD4+ T lymphocytes, the Nef-ADAM17-TNFα axis is part of the mechanism of latent HIV-1 activation. It is noteworthy that these observations have been reproduced using: (1) primary CD4+ T lymphocytes latently infected with HIV-1; (2) exosomes from both primary CD4+ T lymphocytes and macrophages acutely infected with HIV-1; (3) co-cultures of HIV-1 acutely infected CD4+ T lymphocytes and autologous lymphocytes latently infected with HIV-1, and (4) exosomes from cells expressing a defective HIV-1. Conclusions Our results strongly suggest that latent HIV-1 can be activated by TNFα released by cells upon ingestion of exosomes released by infected cells, and that this effect depends on the activity of exosome-associated ADAM17. These pieces of evidence shed new light on the mechanism of HIV reactivation in latent reservoirs, and might also be relevant to design new therapeutic interventions focused on HIV eradication.